Anterior Lumbar Interbody Fusion (ALIF) or Transforaminal Lumbar Interbody Fusion (TLIF) for Fusion Surgery in L5/S1 – What Is the Best Way to Restore a physiological Alignment? - Platz, Uwe; Halm, Henry; Thomsen, Björn; Pecsi, Ferenc; Köszegvary, Mark; Bürger, Nina; Berlin, Clara; Quante, Markus (Zeitschrift für Orthopädie und Unfallchirurgie, 2021)
Study Design A retrospective single center cohort study with prospective collected data from an institutional spine registry.Objectives To determine whether restoration of lordosis L5/S1 is possible with both anterior lumbar interbody fusion (ALIF) and transforaminal lumbar interbody fusion (TLIF) and to find out which technique is superior to recreate lordosis in L5/S1.Methods Seventy-seven patients with ALIF and seventy-nine with TLIF L5/S1 were included. Operation time, estimated blood loss), and complications were evaluated. Segmental lordosis L5/S1 and L4/5, overall lordosis, and proximal lordosis (L1 to L4) were measured in X-rays before and after surgery. Oswesery disability index and EQ-5D were assessed before surgery, and 3 and 12 months after surgery.Results Mean operation time was 176.9 minutes for ALIF and 195.7 minutes for TLIF (p = 0.048). Estimated blood loss was 249.2 cc for ALIF and 362.9 cc for TLIF (p = 0.005). In terms of complications, only a difference in dural tears were found (TLIF 6, ALIF none; p = 0.014). Lordosis L5/S1 increased in the ALIF group (15.8 to 24.6°; p < 0.001), whereas no difference was noted in the TLIF group (18.4 to 19.4°; p = 0.360). Clinical results showed significant improvement in the Oswesery disability index (ALIF: 43 to 21.9, TLIF: 45.2 to 23.0) and EQ-5D (ALIF: 0.494 to 0.732, TLIF: 0.393 to 0.764) after 12 months in both groups, without differences between the groups.Conclusion ALIF and TLIF are comparable methods for performing fusion at L5/S1, with good clinical outcomes and comparable rates of complications. However, there is only a limited potential for recreating lordosis at L5/S1 with a TLIF.
Keywords: lumbar lordosis; spinal fusion; sagittal alignment; lumbosacral fusion